Validasi Modul “Cakap” untuk Meningkatkan Keterampilan Sosial Mahasiswa Baru Asal Bali - Ni Made Yanthi Ary Agustini; Budi Andayani (Faculty of Psychology, Universitas Gadjah Mada, 2017)
Having low social skills can make individuals experience difficulty adjusting to a new environment. The purpose of this research is to validate